Honeycomb-like N/O self-doped hierarchical porous carbons derived from low-rank coal and its derivatives for high-performance supercapacitor. (1st January 2023) - Li, Li; Wei, Xian-Yong; Shao, Chang-Wang; Yin, Fan; Sun, Bing-Kang; Liu, Fang-Jing; Li, Jia-Hao; Liu, Zhong-Qiu; Zong, Zhi-Min
Graphical abstract: Highlights: N/O self-doped HPCs were successfully prepared from several coal derivatives. The HPCs own honeycomb-like hierarchical porous structure with ultrahigh SSA. The HPC from SPLRL has specific capacitance of 373 F g −1 at 0.5 A/g. The assembled supercapacitors exhibit high energy density and power density. The relationship between precursor composition and supercapacitor performance was revealed. Abstract: To maximize the utilization of Xinjiang low-rank coals and increase their added value, soluble portions (SPs) from catalytic ethanolysis of Runbei lignite (RL) and Shaerhu subbituminous coal (SSBC) were used as precursors to prepare hierarchical porous carbons (HPCs). Such HPCs deliver various porous structures. Among them, the HPC prepared from a SP of light RL (SPLRL ) exhibits favorable characteristics for electrochemical performance with honeycomb-like structure, high specific surface area (3586 m 2 g −1 ), high hierarchical pore volume (2.58 cm 3 g −1 ), and rich nitrogen/oxygen doping. As electrode for supercapacitor, the HPC from SPLRL delivers the maximum gravimetric specific capacitance of 373 F g −1 at the current density of 0.5 A g −1 and a reasonable rate capacitance of 300 F g −1 even at 20 A g −1 in 6 M KOH electrolytes with some excellent and stable electrochemical properties. In particular, as a symmetric capacitor electrode, the HPC from SPLRL possesses an excellent capacitive behavior with high energy density (ED) of 11.53 Wh kg −1 at the power density (PD) of 125 W kg −1 and still maintains 9.32 Wh kg −1 at a PD of 5 W g −1 . It also presents superior cycle stability (capacitance retention up to 97.4 % after 10, 000 cycles at 5 A g −1 ). The yields of SPs from catalytic hydrocracking of RL and SSBC reached up to 82.1% and 74.7%, respectively, with 64.6% of phenols in SPLRL determined with a gas chromatograph/mass spectrometer (GC/MS). The possible reaction pathways for the formation of oxygen-containing compounds were explored. In addition, abundant nitrogen- and oxygen-containing compounds were analyzed with an orbitrap mass spectrometer and their possible structures were deduced.